Studi Komparatif Aspek Pengukuran Kinerja Keuangan Sebelum Dan Selama Pandemi Covid - Rahman Pura (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2021)
This study aims to analyze differences in financial performance from the aspects of solvency and profitability before and during the Covid pandemic. The research was conducted at PT Telkomsel. The data is collected using documentation techniques in the form of financial reports based on the first, second and third quarters of 2019 and 2020. The analysis technique uses the Different t Test with the Paired Samples T Test, which compares data before the Covid pandemic (2019) with data during the Covid pandemic ( 2020). The results showed that the solvency value (DER) during the Covid pandemic increased compared to before the Covid pandemic, while the profitability value (ROA) during the Covid pandemic decreased compared to before the Covid pandemic. Then there is a significant difference in financial performance before and during the Covid pandemic both from the solvency aspect as measured by the Debt Equity Ratio (DER) and from the profitability aspect as measured by the Retrun On Assets (ROA) ratio. The research implication is that the high solvency value (DER) and the low profitability value (ROA), if it continues to be prolonged, will have an impact on decreasing the level of trust of creditors or potential creditors and investors or potential investors in the company.